Fertilizing NPK and Compost from Coffee Skins on Long Bean Plants - Umu Khairoh; Made Suarta; Yohanes Parlindungan Situmeang (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2023)
This research aims to examine the influence of NPK fertilizer and coffee husk compost and their combined influence on the growth and yield of long bean plants. The research was carried out in the Greenhouse of the Faculty of Agriculture, Warmadewa University from March to June 2022 using a two-factor randomized block design which was repeated three times. The first factor, NPK fertilizer (M), has four levels, namely M0 = 0 kg ha-1, M1 = 100 kg ha-1, M2 = 200 kg ha-1, M3 = 300 kg ha-1. The second factor, Coffee Skin Compost (K) treatment, consists of four levels: K0 = 0 ton ha-1, K1 = 15 ton ha-1, K2 = 30 ton ha-1, and K3 = 45 ton ha-1. Application of NPK fertilizer at a dose of 300 kg ha-1 resulted in the highest fruit weight of 136.29 g, an increase of 63.36% compared to the lowest fruit weight (83.43 g) in the 0 kg ha-1 NPK fertilizer treatment. Apart from that, the 45-ton ha-1 coffee skin compost treatment produced the highest fruit weight, namely 117.53 g, an increase of 27.58% compared to the lowest fruit weight (92.12 g) in the 0 kg ha-1 coffee skin compost treatment. In particular, the combination of 300 kg ha-1 of NPK fertilizer and 45 tons ha-1 of coffee husk compost produced the highest oven-dry weight, reaching 95.28 g.